Masculinity of Percy Jackson in Heroes of Olympus: House of Hades Novel by Rick Riordan - Hakim, Aji Muhammad Luqmanul; Zamruddin, Mardliya Pratiwi; Sudirman, Eka Pratiwi (Fakultas Ilmu Budaya Universitas Mulawarman, 2023)
This study analyzes the concept of masculinity by Brannon in the novel Heroes of Olympus: House of Hades. The purpose of this study is to describe how forms of masculinity are displayed through the character of Percy Jackson in his practice of applying the behavior of a man in responding to his surroundings. This study uses a qualitative descriptive research design. The data are in the form of narration and dialogue, which are related to forms of masculinity. Data analysis used Brannon theory and then the data analysis process used Miles and Huberman's theory. In the results of this study, researchers found forms of masculinity used by Percy's character for the sake of protecting his friends and lovers from Percy himself. Therefore, Percy Jackson and his masculinities can be taken as representative of human nature in general in terms of being a gentleman for others which is also common happen in current society.